Assessing palliative care need in left ventricular assist device patients and heart transplant recipients. (6th November 2020) - Strangl, Felix; Ullrich, Anneke; Oechsle, Karin; Bokemeyer, Carsten; Blankenberg, Stefan; Knappe, Dorit; Reichenspurner, Herrmann; Bernhardt, Alexander M; Barten, Markus J; Rybczynski, Meike
Abstract: Objectives: Palliative care (PC) has gained rising attention in a holistic treatment approach to chronic heart failure (HF). It is unclear whether there is a need for PC in left ventricular assist device (LVAD) patients or heart transplant recipients. Methods: In a cross-sectional explorative pilot study, outpatients after heart transplantation (HTx, n = 69) or LVAD implantation ( n = 21) underwent screening for palliative care (PC) need and evaluation of symptom burden and psychological distress using tools that emanated from palliative cancer care. Results: The 'Palliative Care Screening Tool for Heart Failure Patients' revealed scores of 4.3 ± 2.2 in HTx and 6.0 ± 2.1 in LVAD patients (max. 12 points, P = 0.003), indicating the need for PC (≥5 points) in 32% of HTx and 67% of LVAD patients. Symptom burden, as assessed by MIDOS ('Minimal Documentation System for Palliative Care') scores was substantial in both groups (4.9 ± 4.7 in HTx vs 6.6 ± 5.3 in LVAD, max. 30 points, P = 0.181). 'Fatigue', 'weakness' and 'pain' were the most frequent symptoms. Using the 'Distress-Thermometer', 'clinically relevant' distress was detected in 57% of HTx and 47% of LVAD patients ( P = 0.445). In the PHQ-4 ('4-Item Patient Health Questionnaire'), 45% of LVAD patients, compared to only 10% of HTx patients, reported mild symptoms of anxiety and depression. Conclusions: Findings reveal substantial need for PC in LVAD patients and, to a lesser extent, in heart transplant recipients, suggesting that multi-disciplinary PC should be introduced into routine aftercare. Abstract : Despite major therapeutic advancements, heart failure (HF) remains associated with a poor prognosis.